Sensation and representation - Bain, D; Bain, David T. (2000)
﻿ There are good reasons for wanting to adopt an intentionalist account of experiences generally, an account according to which having an experience is a matter of representing the world as being some way or other according to which, that is, such mental episodes have intrinsic, conceptual, representational content. Such an approach promises, for example, to provide a satisfying conception of experiences' subjectivity, their phenomenal character, and their crucial role in constituting reasons for our judgements about the world. It promises this, moreover, without incurring the difficulties that face the adverbialist and the friends of such items as qualia and "private objects". Still, even many of those who have been persuaded of that much are inclined to make an exception of the bodily sensations, since pains and the rest have traditionally been taken to be peculiarly "blank" instances of brute, non-conceptual feeling. In this study, I reject that tradition and argue that sensation experiences are indeed representational, and hence not in that respect exceptional. The idea that they are nevertheless distinctive in other ways vis-à-vis ordinary perceptual experiences has led intentionalists such as John McDowell to adopt an account of their content that is both mentalist and radically subjectivist: an account, in other words, that takes the items represented by such experiences to be mental and constitutively dependent on their being represented. To my mind, such subjectivism is both viciously circular like the parallel view of colours and at odds with the admirably intentionalist aspirations of these views. Hence I turn to consider objectivist versions of intentionalism, views that assimilate sensations to somatosensory perceptual experiences such as those that inform us of, for example, the position of our own limbs. Admittedly, these views not only risk losing the "interiority" of sensations, but I argue that they also cannot be combined with mentalism and that this generates considerable difficulties difficulties that have either been ignored or underestimated by those working with less demanding conceptions of content. Nonetheless, I make a number of preliminary moves to show how such difficulties might be dealt with, and how the objectivist can register even the distinctively "inner" character of sensations by, amongst other things, focussing on the peculiarities of somatosensory content. So the prospects for intentionalism about sensations are, I argue, good.